Novel Antibiofilm Compound Using Natural Product against Staphylococcus Aureus and Streptococcus Mutan Considering Biofilm as Real Hazard to Health are System - Naveed Faraz; Tanveer Abbas; Sehrish Shafique (ANNALS OF ABBASI SHAHEED HOSPITAL AND KARACHI MEDICAL & DENTAL COLLEGE, 2026)
Objectives: To evaluate the antibiofilm activities of natural compound, Mango Leaf Extract (MLE) and Pomegranate Peel Extract(PPE) against Staphylococcus aureus and Streptococcus Mutans. Also use the MLE and PPE in combination so we aim to evaluate the synergistic activity of these two compounds against Staphylococcus Aureus and Streptococcus Mutans as an antibiofim agent because biofilm formation is the main virulence factor of microorganisms to provide resistance against antibiotics.Methods: 96 well plate method is used to evaluate biofilm forming activity of organism as well as used for evaluating antibiofilm forming activity of mango leaf extract and pomegranate peel extract individually and in combination.Results: The individual antibiofilm concentrations of pomegranate and mango leaf extract were 41.66 ± 11.78 mg/ml and 20.83 ± 5.89 mg/ml, respectively against Staphylococcus Aureus. However, when combined, the effective antibiofilm concentrations dropped to 3.46 ± 2.38 mg/ml (pomegranate) and 3.56 ± 2.41 mg/ml (mango leaves). Whereas the antibiofilm activity of PPE & MLE against Streptococcus Mutans individually were 33.3 ± 3.33 mg/ml and 16.66 ± 5.88 mg/ml, respectively. However, in combination, the required concentrations decreased significantly antibiofilm activity to 8.36 ± 2.92 mg/ml for pomegranate peel and 3.61 ± 2.38 mg/ml for mango leaves. Both gram positive cocci show significant resistance against tested antibiotics.Conclusion: Mango leaf extract and Pomegranate peel extract has shown good antibiofilm activity against Staphylococcus Aureus and Streptococcus Mutans individually as well as in combination shows synergistic activity. Whereas both organisms show resistance against conventional antimicrobial agents. We can use MLE and PPE as an antibiofilm individually as well as in combination. In this way provide the alternative adjuvant product with the conventional antibiotic which is free from adverseeffect as well as cost effective and have alternate option to minimize resistant microorganism survival.